RELATIONSHIP OF PARENTING PATTERNS WITH INCIDENCE OF NUTRITION IN CHILDRENIN SUB-DISTRI BARAN TIMUR MERAL KARIMUN DISTRICTS - Agung Hadi Pranomo; Dino Gagah Prihadianto (Universitas Batam, 2020)
Background : Based on data from the Karimun District Health Office in 2017, there was 0.9% malnutrition, 4.8% malnutrition, and the prevalence of underweight children was 5.7%. Meanwhile, according to the Center for Data and Information, the Ministry of Health of the Republic of Indonesia in 2017 the nutritional status of children under five to 59 months according to BW / U has 3.7% malnutrition, 14.0% malnutrition, 80.1% good nutrition and 2.1% over nutrition. The purpose of this study was to determine the relationship between maternal knowledge and parenting about the nutritional status of toddlers with the incidence of malnutrition in children under five in Baran Timur Village, Meral District, Karimun Regency. Method : This research used an analytical research design with a cross sectional design approach. Meral Karimun Regency. In this study, the population is all mothers who have toddlers aged 3-59 months who live in Baran Timur Village, Meral District, Karimun Regency as many as 460 people. The data is presented in the form of a cross table then the data is analyzed using the SPSS program (Social Science Program Statistics) through the chi-square statistical test using a significant level of 0.05 Result : from 82 respondents, it is found that 1 respondent (33.3%) with less parenting is malnutrition status, 1 respondent (33.3%) with poor parenting was malnourished and 1 respondent (33.3%) with insufficient parenting was good nutritional status. While 21 respondents (63.6%) with moderate parenting were good nutritional status and 41 respondents (89.1%) with good parenting were good nutritional status obtained a p value of 0.003